Recent strategies to develop self-healable crosslinked polymeric networks. Issue 66 (25th August 2015) - An, So Young; Arunbabu, Dhamodaran; Noh, Seung Man; Song, Young Kyu; Oh, Jung Kwon
<x xml:space="preserve">Abstract</x> Autonomous self-healable crosslinked materials designed with built-in ability to repair physical damage and cracks can prevent catastrophic failure and thus extend the lifetime of materials.